Effects of RARα ligand binding domain mutations on breast fibroepithelial tumor function and signaling - Xi Xiao Huang; Ley Moy Ng; Po-Hsien Lee; Peiyong Guan; Mun Juinn Chow; Aisyah Binte Mohamed Bashir; Meina Lau; Kenric Yi Shu Tan; Zhimei Li; Jason Yongsheng Chan; Jing Han Hong; Sheng Rong Ng; et al. (npj Breast Cancer)
Abstract Point mutations in the ligand binding domain of retinoic acid receptor alpha (RARα) are linked to breast fibroepithelial tumor development, but their role in solid tumorigenesis is unclear. In this study, we assessed the functional effects of known RARα mutations on retinoic acid signaling using biochemical and cellular assays. All tested mutants exhibited reduced transcriptional activity compared to wild-type RARα and showed a dominant negative effect, a feature associated with developmental defects and tumor formation. X-ray crystallography revealed that the mutants maintained structural integrity, with altered co-activator recruitment explaining the loss of transcriptional function. Transcriptomics and cell growth assays demonstrated that mutant RARα proteins conferred resistance to ligand-induced growth inhibition in phyllodes tumor cells. Although the mutations impair RARα’s response to retinoic acid, some mutants could be partially reactivated with synthetic agonists. These findings provide insights into how RARα mutations may contribute to tumorigenesis.